Gaming Experiments for Analysis of Pricing Mechanisms at Electricity Markets. Issue 32 (2016) - Chirkin, V.; Goldstein, M.; Gorbunov, A.; Goubko, M.; Korepanov, V.; Korgin, N.; Sayfutdinov, T.; Sharova, A.; Vaskovskaya, T.
Abstract: A method is proposed to support management policy design and verification in complex cyber-physical & human systems (CPHS). A hierarchy of interconnected formal models is built to provide the multi-faceted view of the conflict situation lying in the core of a certain management problem. Game-theoretical analysis reveals the problem and mechanism design suggests the alternative management policy. Its efficiency is verified by multi-agent simulations and gaming experiments with experts. The approach is illustrated using the examples of two market manipulation issues arising on the Russian wholesale electricity market.